(untitled) (Research in Agriculture Livestock and Fisheries, 2024)
The study was conducted to compare midline and flank approaches for spaying in cats. Cats were divided into two groups based on surgical approaches for spaying, Group A (Flank approach) and Group- B (Ventral midline approach). To evaluate the best approach for spaying, various parameters such as length of the surgical incision, the extent of haemorrhage, ease of location and exteriorization of ovaries and uterus, duration of surgery, postoperative complications, and time required for complete wound healing were recorded. In addition, the heart rate, respiration rate, and temperature were recorded before the operation and on different days after the operation. The physical parameters significantly (P<0.05) differed between the two groups. In both groups, the average length of skin incision was 2.8 cm. The average time of exteriorization of ovaries and uterus was higher in the ventral midline approach as compared with the flank approach. The average duration of surgery was (23.25±4.20) min in group A and 29·25±4.88 min in group B. The average wound healing time (days) was also higher in the ventral midline approach (16.50±1.26) compared to the flank approach (13.75±7.85). During Spaying in cats, the extent of haemorrhage was mild to moderate in the flank approach, whereas there was no haemorrage or sometimes less in the ventral midline approach. The post-operative complications were less in flank methods than in ventral midline approaches. It is concluded that spaying through the flank approach is superior to the ventral midline approach due to convenience, faster healing, rapid recovery, and fewer postoperative complications. Vol. 10, No. 3, December 2023: 319-326